What are the optimal measures to identify anxiety and depression in people diagnosed with head and neck cancer (HNC): a systematic review - Chindhu Shunmugasundaram; Claudia Rutherford; Phyllis N. Butow; Puma Sundaresan; Haryana M. Dhillon (SpringerOpen, 2020)
Abstract Background A cancer diagnosis is potentially life-threatening, likely causing distress and uncertainty, which may be psychologically debilitating. Depression and anxiety are commonly underdiagnosed and undertreated in cancer patients. Head and neck cancer (HNC) patients face particular challenges that may contribute to distress. This review aims to: i) identify patient reported outcome measures (PROMs) designed to assess anxiety and depression in HNC; and ii) determine their suitability for use in research and clinical practice to screen patients. Methods We searched five electronic databases between July 2007 to July 2019 for studies assessing anxiety and depression in HNC patients. Searches were limited to this period to account for advances in cancer treatment. Records were screened for eligibility by one reviewer and 10% cross-checked by a second across all stages of the review. In addition to the electronic searches, PROM databases were searched for additional measures of anxiety and depression. All retrieved PROMs were mapped against Diagnostic and Statistical Manual-5 criteria for anxiety and depression to assess content coverage. Then, their psychometric properties appraised against the COSMIN checklist. Results Electronic searches identified 98 records, from which five anxiety and eight depression measures were retrieved. PROM database searches retrieved an additional four anxiety and four depression measures; a total of nine anxiety and 12 depression measures were appraised. Content coverage of anxiety measures ranged from 50% to 75% and depression measures from 42% to 100%. Demonstration of psychometric properties against COSMIN criteria ranged from 57% to 71% for anxiety measures (three PROMs > 70%) and from 29% to 86% for depression measures (nine PROMs > 70%). Three anxiety and seven depression measures had established clinical cut-offs in cancer populations. Conclusions The Patient Health Questionnaire-9, Zung Self-rating Depression and Zung Self-rating Anxiety Scales demonstrated good content coverage along with excellent psychometric properties, and thus were considered the most suitable PROMs to assess psychological distress in HNC populations. It is important to have PROMs assessing psychological distress that capture a comprehensive set of subjective symptoms. The identified PROMs will help researchers and health professionals in clinical-decision making, thereby potentially improving quality of life in HNC patients.